1998
DOI: 10.1055/s-2007-1001421
|View full text |Cite
|
Sign up to set email alerts
|

Is Urinary Bladder Pressure a Sensitive Indicator of Intra-Abdominal Pressure?

Abstract: We concluded that bladder pressure measured by transurethral catheter was equal to insufflator pressure during laparoscopy, and that this was a valid indicator of intra-abdominal pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 0 publications
2
25
0
4
Order By: Relevance
“…3,7,10) However, measurement of intra-abdominal pressure with a transurethral bladder catheter in 84 morbidly obese patients found that higher sagittal abdominal diameter was associated with significant increase in this pressure. 8) Intra-abdominal pressure was well above 8 mmHg and could be as high as 12 mmHg in some obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,10) However, measurement of intra-abdominal pressure with a transurethral bladder catheter in 84 morbidly obese patients found that higher sagittal abdominal diameter was associated with significant increase in this pressure. 8) Intra-abdominal pressure was well above 8 mmHg and could be as high as 12 mmHg in some obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tekanan intra abdomen akan naik bila volume cavum abdomen meningkat secara akut dan melebihi kapasitas yang dimilikinya. Apabila terjadi peningkatan tekanan intra abdomen yang ekstrim dapat terjadi sindroma kompartemen abdomen yang meliputi gangguan pada mekanisme respirasi, hemodinamika dan fungsi ginjal (6,7).…”
Section: Pendahuluanunclassified
“…Lavase peritoneal diagnosis (LPD) suatu metode untuk menunjang menegakkan diagnosis dari cedera intra abdomen telah digunakan secara luas karena dianggap cukup obyektif dalam menilai adanya cedera intra abdomen. Meskipun tehniknya relatif mudah dengan angka ketepatan yang melampaui 95%, dengan komplikasi sekitar 1% yaitu adanya cedera vaskuler dan perforasi organ berongga (6,7,8). Namun karena bersifat invasif dan tidak bersifat spesifik untuk organ tertentu, pemeriksaan memerlukan waktu dan menunggu hasil pemeriksaan laboraorium dan harus dengan persiapan untuk langsung melakukan laparotomi.…”
unclassified
“…To provide such validation, studies must be conducted where intraabdominal pressure is measured directly in patients by placement of intraperitoneal catheters. 43,44 These techniques are not standard practices in the ICU, and their use would significantly increase the risk to patients and cannot be ethically justified. The lack of direct measurement of intra-abdominal pressure is a limitation of the present study, as with all other clinical studies assessing the effects of the volume of saline instilled into the patient's bladder and position on IBP.…”
Section: Clinical Implications and Future Researchmentioning
confidence: 99%